Ethylene Insensitive 3-Like 2 is a Brassicaceae-specific transcriptional regulator involved in fine-tuning ethylene responses in Arabidopsis thaliana - Houben, Maarten (Journal of experimental botany, 2022)
© The Author(s) 2022. Published by Oxford University Press on behalf of the Society for Experimental Biology. All rights reserved. For permissions, please email: journals.permissionsoup.com.